Primary ovarian pregnancy: histopathology remains the key to confirming diagnosis setting - Anand, Priyanka; Nargotra, Namrata (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Ectopic pregnancy occurs in 2% of all pregnancies. Primary ovarian pregnancy is a rare entity and accounts for only 0.15-3% of all ectopic gestations. It usually ends with rupture before the end of first trimester. The diagnosis is often made intraoperatively and confirmed histopathologically. A 23 year old female presented with severe hypogastric abdominal pain with no history of amenorrhea. She underwent a laprotomy and a right sided salpingo-oopherectomy and the excised material was sent for histopathological examination. Chorionic villi were seen within the ovarian stroma suggesting the likely possibility of an ovarian pregnancy. Ovarian pregnancy is rare; although awareness of this condition is important for reducing its associated morbidity and mortality. This highlights the importance of histopathology for the accurate diagnosis of this condition.